Performance, diarrhea frequency, feces production and costs of diets with increasing levels of pineapple byproducts in weaned piglets - Ramos, G. F. [UNESP]; Junior, C. D. S. [UNESP]; Oliveira, J. A. [UNESP]; Vasconcelos, T. S. [UNESP]; Budino, F. E. L.; Ruiz, U. S. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2016)
This research aimed to evaluate diets with growing levels of pineapple meal in weaned piglets feeding. Fifty-six piglets, from 21 to 63 days old, were fed diets composed mainly of corn, soybean meal, and dairy products, with the addition of pineapple byproduct in 0%, 3.4%, 6.8% and 10.2%. The parameters evaluated were: growth performance; diarrhea incidence; excretion in feces, total and per unit of weight gain, of dry (DM), mineral (MM) and organic (OM) matters, nitrogen (N) and phosphorous (P); diet costs related to weight gain, index of economic efficiency and of costs. The evaluations were performed from 21 to 35 days; from 21 to 49 days; and from 21 to 63 days of age. A complete randomized block design was adopted, according to the animal's weight in the beginning of the trial, with four treatments and seven repetitions. From day 21 to 49 the animals fed diets with 3.4 and 6.8% of pineapple meal consumed more feed (P<0.05) than those fed the control diet, and from day 21 to 63 only the animals that received the diet with 3.4% of pineapple presented a higher weight gain (P<0.05) than control piglets. From day 21 to 63 animals fed diets with pineapple meal presented higher (P<0.05) excretions of DM, MM, OM, and N than the control animals. However, checking the excretions of these components in the feces per unit of live weight gain in the same period, it was found that there was no difference (P>0.05) among the piglets fed diets without pineapple meal and those who consumed the diet with 3.4% of the product. Thus, the inclusion of pineapple meal in weaned piglet's diets at 3.4% is feasible, because it did not interfere negatively on excretions per unit of live weight gain and in diet cost indices, and provided better weight gain to the animals, as compared with pigs who did not consume pineapple meal.
Keywords: dietary fiber; excretion of residues; weight gain